A “Ballpark” Assessment of Efficiency in Social Distancing in Early Fights against the COVID-19 Pandemic - Kim, Tae Jong; Kim, Hyosun (KDI School of Public Policy and Management, 2021)
This paper presents results from assessment of efficiency in social distancing in international responses to the COVID-19 pandemic in 2020. The simple framework adopted for the assessment recognizes two kinds of costs that a society may bear in a pandemic. The first is costs due to infection (infection costs); the second costs resulting from slowdown in economic transactions (economic costs). Efficient social distancing should minimize the sum of these costs. Infection costs are likely to decrease with social distancing at a decreasing rate as intensified social distancing eases pressure on scarce resources for intensive care. Economic costs on the other hand are likely to increase at an increasing rate as extreme slowdown in economic life may entail job losses and business failures. The resulting U-shaped total costs curve implies parity between infection costs and economic costs as a necessary condition for efficiency. In a simplified implementation of the framework, we approximate infection costs by the value of (statistical) lives lost, and economic costs by the gap between the actual gross domestic product in 2020 and the potential GDP as predicted by the within-country growth trend during the preceding decade. The results for 158 countries suggest that the global community perhaps reacted with overly strict social distancing measures whereas high-income countries as a group were more successful in maintaining the parity between infection and economic costs.
Keywords: COVID-19; Social Distancing; Economic and Infection Costs related to Pandemics; Efficiency